PERBEDAAN RASIO NEUTROFIL-LIMFOSIT DAN C-REACTIVE PROTEIN PADA IBU HAMIL DENGAN COVID-19 TANPA DAN DISERTAI PREEKLAMPSIA Penelitian di RSUD Ulin Banjarmasin Periode Maret 2020 - Periode Maret 2020-Februari 2022 - Qaedi, Muhammad Bari Nur; Armanza, Ferry; Hendriyono, Fransiskus Xaverius; Aditya, Renny; Rahmiati, Rahmiati (Universitas Lambung Mangkurat, 2023)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. Pregnant women are vulnerable to COVID-19. Preeclampsia is a complication in pregnant women characterized by hypertension at > 20 weeks of gestation and proteinuria. The Neutrophils Lymphocyte Ratio and C-Reactive Protein is a marker of inflammation related to disease severity. Elevated NLR and CRP are associated with COVID-19 and preeclampsia. The study aims to determine whether there are significant differences in NLR values or CRP levels for pregnant women with COVID-19 without and with preeclampsia. This type of research is analytic observational using a retrospective cross-sectional study. The results of the study were 603 subjects, 70 subjects met the inclusion criteria. Subjects of pregnant women with COVID-19 without preeclampsia were randomized, obtained 30 subjects of pregnant women with COVID-19 without preeclampsia and 30 subjects accompanied by preeclampsia. The NLR value of pregnant women with COVID-19 without preeclampsia had a median of 5.57, a minimum value of 1.90 and a maximum value of 30.38. Those accompanied by preeclampsia had a median of 5.13, a minimum value of 2.04 and a maximum value of 18.10. CRP levels of pregnant women with COVID-19 without preeclampsia had a median of 45.2 mg/L, a minimum value of 2.0 mg/L and a maximum value of 240.0 mg/L. Those accompanied by preeclampsia had a median of 50.4 mg/L, a minimum value of 2.6 mg/L and a maximum value of 318.1 mg/L. Conclusion: there was no significant difference in NLR values or CRP levels in pregnant women with COVID-19 without and with preeclampsia (p=0.631, p=0.478).